Contested territories and international law : a comparative study of the Nagorno-Karabakh conflict and the Aland Islands precedent - Makili-Aliyev, Kamal, 1985- (Routledge, 2019)
"This book considers the possibilities for resolution of the Nagorno-Karabakh Conflict in the context of comparative international law. The armed conflict between Armenia and Azerbaijan over the territory of the Nagorno-Karabakh has been on the peace and security agenda since the dissolution of the Soviet Union. This volume draws parallels with a similar situation between Sweden and Finland over sovereignty of the Aland Islands in the early 20th Century. Resolved in 1921, it is argued that this represents a model autonomy solution for territorial conflicts that include questions of territorial integrity, self-determination and minority rights. The book compares both conflict situations from the international law perspective, finding both commonalities and dissimilarities. It advances the application of the solution found in the Aland Islands precedent as a model for the resolution of the Nagorno-Karabakh Conflict, and provides appropriate recommendations for its implementation"-- Provided by publisher
Keywords: Nagorno-Karabakh Conflict, 1988-1994.; Åland question.; International law.; Nagorno-Karabakh (Azerbaijan) -- International status.; Conflit du Nagorno-Karabakh, 1988-1994.; Question d'Åland.; Nagorno-Karabakh (Azerbaïdjan) -- Statut international.; LAW -- General.; LAW -- Comparative.; LAW -- International.; Åland question; International law; Azerbaijan -- Nagorno-Karabakh; 1988-1994